2011
DOI: 10.1016/j.ygeno.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a de novo genome-wide computational approach for updating Brachypodium miRNAs

Abstract: Plant microRNAs (miRNAs) are single-stranded 20-22 nt small RNAs (sRNA) that are produced from their own genes. We have developed a de novo genome-wide approach for the computational identification of novel plant miRNAs based on the integration of the complete genome sequence with sRNA libraries. It comprises three modules - the clustering module identifies genomic regions that have two closely-located unidirectional sRNA clusters, the mirplan module explores the secondary structure of the genomic regions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…In the present study, we have used next-generation sequencing (NGS) technology to annotate and profile the expression of conserved and non-conserved miRNA and miRNA-like molecules during Brachypodium leaf development along the proximo–distal axis and compare miRNA expression along this axis during normal and severe drought conditions. Specifically, we have identified a total of 270 miRNA and miRNA-like genes, confirming 66 previous annotations (Unver and Budak, 2009; Wei et al, 2009; Zhang et al, 2009; Baev et al, 2011) and adding 28 additional loci from known miRNA families as well as 94 novel miRNA genes plus 82 siRNA-like miRNA loci. Differential expression analyses suggest that a number of miRNAs are involved in developmental reprogramming of leaf growth in response to drought.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…In the present study, we have used next-generation sequencing (NGS) technology to annotate and profile the expression of conserved and non-conserved miRNA and miRNA-like molecules during Brachypodium leaf development along the proximo–distal axis and compare miRNA expression along this axis during normal and severe drought conditions. Specifically, we have identified a total of 270 miRNA and miRNA-like genes, confirming 66 previous annotations (Unver and Budak, 2009; Wei et al, 2009; Zhang et al, 2009; Baev et al, 2011) and adding 28 additional loci from known miRNA families as well as 94 novel miRNA genes plus 82 siRNA-like miRNA loci. Differential expression analyses suggest that a number of miRNAs are involved in developmental reprogramming of leaf growth in response to drought.…”
Section: Introductionsupporting
confidence: 76%
“…While an increased density of miRNAs on chromosome 1 and chromosome 3 was reported previously (Baev et al, 2011), we observed no distinct clustering of miRNA genes across the five chromosomes (Figure 4). Notably, for two miRNA genes ( miR5198 , miR5201 ), we confirmed the genomic localization annotated in miRBase, but we propose a new miRNA:miRNA* duplex that corresponds to the most abundant sequences found in our library.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Plant miRNAs have been well characterized in several model systems for plant genomics such as Arabidopsis, Brachypodium, Oryza and Populus [16]. They are single-stranded 20–22 nt small RNAs that are endogenously produced from their own genes [2].…”
Section: Introductionmentioning
confidence: 99%